Measuring the effect of receptive and productive vocabulary size on foreign language skills - Yilmaz, Selahattin; Kavanoz, Suzan (UNIV GRANADA, 2025)
Vocabulary knowledge is crucial for developing English language skills, and assessing students' vocabulary levels offers an effective means to monitor their language development and predict their test performance. Therefore, this study examined the relationship between receptive and productive vocabulary knowledge and English language skills (reading, writing, listening, speaking, and use of English) of 306 Turkish university students enrolled in A1, A2, and B1-level EFL classes as part of a preparatory language program. Vocabulary knowledge was measured using a receptive and a productive vocabulary levels test, while language skills were assessed through an English Proficiency Exam and a speaking exam. The results revealed significant positive correlations between receptive and productive vocabulary knowledge, particularly at higher proficiency levels. Receptive vocabulary was found to be a much stronger predictor of language skills, especially for reading, listening, and use of English (UoE), than productive vocabulary which predicted performance in UoE. The impact of both vocabulary tests was more pronounced at higher proficiency levels, although their overall influence on language skills was limited. These findings suggest a nuanced relationship between vocabulary and language proficiency, while highlighting the need for systematic and balanced L2 instruction that includes different dimensions of vocabulary knowledge.
Keywords: english as a foreign language; receptive vocabulary; productive vocabulary; vo-cabulary levels tests; vocabulary instruction; KNOWLEDGE; LEARNERS; 2ND-LANGUAGE; ENGLISH; Education & Educational Research; Linguistics